Buckling Of Cones With Imperfect Length Subjected To Axial Compression - Ifayefunmi, Olawale; Wang, Sheng Hue; Mahidan, Fairuz Mardhiah (TJPRC Pvt. Ltd., 2019)
The paper considers the effect of imperfect length on the buckling behavior of mild steel truncated cone subjected to axial compression. The contact interaction problem between the rigid plate and the cone was successfully benchmarked against experimental data on axially compressed cone with imperfection amplitude-to-thickness ratio, A/t = 0.28 and 5.6. Conical shells are assumed to be made from mild steel with the following geometric properties: big radiusto-small radius ratio, r2/r1 = 2.0; small radius-to-thickness ratio, r1/t = 25; axial length-to-big radius ratio, L/r2 = 2.24; nominal wall thickness, t = 1 mm and cone angle, β = 12.6°. A total of fifteen (15) mild steel cones were collapsed by axial compression. Ten samples with A/t of 0.28 and another five samples with A/t of 5.6. Experimental and numerical load carrying capacity for imperfect cones were obtained for both cases above. The results indicate that imperfection amplitude strongly affect the buckling strength of conical shells. In addition, it was observed that as the magnitude of imperfect length to wall thickness increases, the contact interaction between the cone and the rigid plate changes. Finally, the effect of number of waves on buckling load of cones under axial compression is less significant